Metallic-Nanoparticle-Based Sensing: Utilization of Mixed-Ligand Monolayers - Zeiri, Offer (ACS sensors, 2020)
The last two decades have seen great advancements in fundamental understanding and applications of metallic nanoparticles stabilized by mixed-ligand monolayers. Identifying and controlling the organization of multiple ligands in the nanoparticle monolayer has been studied, and its effect on particle properties has been examined. Mixed-ligand protected particles have shown advantages over monoligand protected particles in fields such as catalysis, self-assembly, imaging, and drug delivery. In this Review, the use of mixed-ligand monolayer protected nanoparticles for sensing applications will be examined. This is the first time this subject is examined as a whole. Mixed-ligand nanoparticle-based sensors are revealed to be divided into four groups, each of which will be discussed. The first group consists of ligands that work cooperatively to improve the sensors’ properties. In the second group, multiple ligands are utilized for sensing multiple analytes. The third group combines ligands used for analyte recognition and signal production. In the final group, a sensitive, but unstable, functional ligand is combined with a stabilizing ligand. The Review will conclude by discussing future challenges and potential research directions for this promising subject.